2012
DOI: 10.1073/pnas.1213960109
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective efficacy of aminopropyl carbazoles in a mouse model of amyotrophic lateral sclerosis

Abstract: We previously reported the discovery of P7C3, an aminopropyl carbazole having proneurogenic and neuroprotective properties in newborn neural precursor cells of the hippocampal dentate gyrus. We have further found that chemicals having efficacy in this in vivo screening assay also protect dopaminergic neurons of the substantia nigra following exposure to the neurotoxin 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine, a mouse model of Parkinson disease. Here, we provide evidence that an active analog of P7C3, known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
106
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(110 citation statements)
references
References 28 publications
(45 reference statements)
4
106
0
Order By: Relevance
“…22). In this model, using mice expressing a high level of a human transgene encoding a mutated variant of the gene encoding human Cu,Zn superoxide dismutase (23)(24)(25)(26)(27), we have observed the same hierarchy of activities wherein P7C3A20 is active, P7C3 is intermediately active, and Dimebon is inactive (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22). In this model, using mice expressing a high level of a human transgene encoding a mutated variant of the gene encoding human Cu,Zn superoxide dismutase (23)(24)(25)(26)(27), we have observed the same hierarchy of activities wherein P7C3A20 is active, P7C3 is intermediately active, and Dimebon is inactive (22).…”
Section: Discussionmentioning
confidence: 99%
“…22). In this model, using mice expressing a high level of a human transgene encoding a mutated variant of the gene encoding human Cu,Zn superoxide dismutase (23)(24)(25)(26)(27), we have observed the same hierarchy of activities wherein P7C3A20 is active, P7C3 is intermediately active, and Dimebon is inactive (22). If the more active variants of this class of compounds indeed possess neuroprotective properties, and if we can rely on the relatively rapid in vivo assay of enhanced neurogenesis to rank order compounds for SAR scoring, it should be possible to optimize variants with the goal of selecting an appropriately qualified chemical to advance for human testing.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless, our findings demonstrate that it is possible to modify astrocytemotor neuron interaction by enhancing NAD ϩ salvage pathway in the astrocytes. Interestingly, aminopropyl carbazole derivatives previously shown to preserve motor function in hSOD1 G93A mice have been recently identified as NAMPT activators (71,72). In summary, because we have shown that therapeutic targets identified in this co-culture system may have a beneficial effect when translated into animal models of ALS (45), our data suggest that further investigation regarding the therapeutic potential of increasing NAD ϩ availability to prevent astrocyte-mediated motor neuron death in ALS is deserved.…”
Section: Discussionmentioning
confidence: 92%
“…A potent P7C3 analogue (P7C3A20, 1.11b, Figure 1.2) is characterized in mice models of PD [137] and ALS [138]. It prevents 1-methyl-4-phenylpyridinium (MPP + )-mediated death of dopaminergic neurons in C. elegans and preserves worm mobility (≈80% protection and mobility preservation at 10 mM), with P7C3 being less active (≈50% protection and ≈60% mobility preservation at 10 mM) [137].…”
Section: Molecular Targets Affinity Rangementioning
confidence: 99%